2003
DOI: 10.1124/jpet.102.048025
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Recognition of OX1 and OX2Receptors by Orexin Peptides

Abstract: In this study, we have compared the abilities of orexin-A and orexin-B and variants of orexin-A to activate different Ca 2ϩ responses (influx and release) in human OX 1 and OX 2 receptorexpressing Chinese hamster ovary cells. Responses mediated by activation of both receptor subtypes with either orexin-A or -B were primarily dependent on extracellular Ca 2ϩ , suggesting similar activation of Ca 2ϩ influx as we have previously shown for orexin-A and OX 1 receptors. Amino acid-wise truncation of orexin-A reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 30 publications
6
125
0
Order By: Relevance
“…Nevertheless, it appears that the contribution of OX 1 receptors to the antiallodynic effect of intrathecal orexins is greater than that of OX 2 receptors. The finding that orexin A was more potent than orexin B may be attributed to the fact that orexin A displays 10-to 100-fold higher affinity for the OX 1 receptors than orexin B (Ammoun et al, 2003). P 2X Purinergic and Glycine, but not Opioid, Receptors are Involved in the Antiallodynic Effects of Orexins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it appears that the contribution of OX 1 receptors to the antiallodynic effect of intrathecal orexins is greater than that of OX 2 receptors. The finding that orexin A was more potent than orexin B may be attributed to the fact that orexin A displays 10-to 100-fold higher affinity for the OX 1 receptors than orexin B (Ammoun et al, 2003). P 2X Purinergic and Glycine, but not Opioid, Receptors are Involved in the Antiallodynic Effects of Orexins.…”
Section: Discussionmentioning
confidence: 99%
“…It might be attributed to the differences in the administration time of orexin B or in the pain animal models (Yamamoto et al, 2002). The mechanism(s) involved in chemically induced inflammatory pain and incision-induced mechanical allodynia might be different, such as the extent of sensory neuron sensitization and the pattern of spinal excitatory amino acid release (Vandermeulen and Brennan, 2000 Given that the antiallodynic effect of orexin B was not completely antagonized by SB-334867 and that orexin B has higher binding affinity for OX 2 than for OX 1 receptors (Ammoun et al, 2003), the possibility that the effect of orexin B is also mediated by OX 2 receptors remains to be elucidated. Nevertheless, it appears that the contribution of OX 1 receptors to the antiallodynic effect of intrathecal orexins is greater than that of OX 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This is frequently observed in heterologous expression systems with both OX 1 R and OX 2 R (Smart et al, 1999;Holmqvist et al, 2002;Ammoun et al, 2003) and is likely to be a consequence of activation of phospholipase C (PLC) and the generation of IP 3 . Some studies on native receptors in neurons have demonstrated sensitivity to inhibitors of phosphatidylinositol-specific PLC (Zhu et al, 2003;Muroya et al, 2004), suggesting that some store release may take place.…”
Section: Discussionmentioning
confidence: 99%
“…The localisation of the orexin proteins is widespread, but there are distinct differences between the two orexin subtypes and their receptors. While ORA is equipotent for OX1R and OX2R, ORB has an w10-fold higher affinity for the OX2 receptor subtype (Ammoun et al 2003). Additionally, the two receptor types appear to have differentially regulated b-arrestin-binding and internalisation profiles (Pfleger et al 2006).…”
Section: Introductionmentioning
confidence: 99%